Cam-follower mechanism for airborne ultrasound generation. (November 2021) - Danakas, Philippe; Bilodeau, Maxime; Quaegebeur, Nicolas
Abstract: In this paper, a novel air-coupled concept for high Sound Pressure Level (SPL) and broadband ultrasound generation is presented. The approach is to convert a rotational motion of an electric motor into a multi-period translation motion using a miniature cam-follower mechanism and a sinusoidal cam profile. The design allows the fundamental frequency and generated SPL to be independent of any mechanical resonance phenomenon. A simplified electro-mechanical analysis of the concept is derived in order to obtain the influence of design parameters on the electrical and acoustic performance of the mechanism. Finally, experimental tests are performed on a prototype that has been able to generate up to 120 dB at 1 m and a maximal fundamental frequency of 23 kHz.